The Stability of Intelligence From Age 11 to Age 90 Years - Deary, Ian J.; Pattie, Alison; Starr, John M. (Psychological Science, 2013)
As a foundation for studies of human cognitive aging, it is important to know the stability of individual differences in cognitive ability across the life course. Few studies of cognitive ability have tested the same individuals in youth and old age. We examined the stability and concurrent and predictive validity of individual differences in the same intelligence test administered to the same individuals (the Lothian Birth Cohort of 1921, N = 106) at ages 11 and 90 years. The correlation of Moray House Test scores between age 11 and age 90 was .54 (.67 when corrected for range restriction). This is a valuable foundation for estimating the extent to which cognitive-ability differences in very old age are accounted for by the lifelong stable trait and by the causes of cognitive change across the life course. Moray House Test scores showed strong concurrent and predictive validity with “gold standard” cognitive tests at ages 11 and 90.